Modelling and Analysing Deadlock in Flexible Manufacturing System using Timed Petri Net (International Journal of Engineering Materials and Manufacture, 2017)
Flexible manufacturing system (FMS) has several advantages compared to conventional systems such as higher machine utilization, higher efficiency, less inventory, and less production time. On the other hand, FMS is expensive and complicated. One of the main problems that may happen is the deadlock. Deadlock is a case that happens when one operation or more are unable to complete their tasks because of waiting of resources that are used by other processes. This may occur due to inappropriate sharing of the resources or improper resource allocation logic which may lead to deadlock occurrence due to the complexity of assigning shared resources to different tasks in an efficient way. One of the most effective tools to model and detect the deadlocks is the petri net. In this research the Matlab software has been used to detect the deadlock in two parallel lines with one shared machines. The analysis shows that deadlock exists at transition with high utilization and place with high waiting time